Safe hospitals e-tool a comparative analysis of the disaster-readiness of private tertiary hospitals using a computer-based assessment tool - Sese, Christian Abelardo M. (College of Architecture, University of the Philippines Diliman, 2011)
This paper carried out a comparative analysis on selected tertiary hospitals in the Philippines using a computer-based assessment tool (CBAT) developed by the researcher with the functionality of a localized Hospital Safety Index. In line with the "Hospitals Safe from Disasters" program of the World Health Organization, a hospital safety index or a hospital disaster-readiness evaluation tool should be established and implemented here in the Philippines suitable to local codes and conditions. There are already existing assessment tools both local and abroad, but in the local context, a quantifiable assessment tool is yet to be developed. This computer-based assessment tool was based on these existing tools, adapting their significant checkpoints and giving them corresponding mathematical weights based on their importance and contribution to the hospital's disaster-readiness. Data acquired from the e-tool was stored in a database, which in the future, as the need arises, can be accessible to the hospital administration, the Department of Health, the safe hospital mitigation group and other authorized parties concerned for reference. Selected private tertiary hospitals in the Philippines were evaluated using this e-tool for comparative analysis on their disaster-readiness and to establish the applicability of such a tool in the local context in producing potential results which merit the same effects as the Hospital Safety Index initiative. The paper also explored the acceptability of such a disaster-readiness tool to hospital owners, administrators and local health professionals as well as professionals in the built environment in an effort to advocate safe hospital design and construction for developing countries.